Aspek Pengembangan Peserta Didik Berbasis Karakter: Studi Literatur - L, Ramli; Yuspiani, Yuspiani; Wahyuddin, Wahyuddin (Indo-MathEdu Intellectuals Journal, 2024)
Education is the most important thing for students as a guide to live life. In this case, the educational process must be designed specifically in terms of developing students' cognitive, affective and psychomotor abilities. These three aspects need to be developed comprehensively so that students' academic, social, and creative abilities can be realized to the maximum. This study uses a literature review method to analyze various sources related to the development of character-based student development. Data collection includes extensive searches in academic datasbases, libraries, and online resources using keywords such as educational character, student development, and character-based learning. The analysis involves thematic categorization, where key themes and patterns are identified, compared, and critically assessed to generate insights into character-based student development principles and practices. The results of the study show that the aspect of student development anytime and anywhere needs change and that through learning (reading and writing) will bring change (behavior change and knowledge) which in essence realizes new skills. Students in giving grades or learning outcomes whether the cognitive realm, affective realm and picicomotor realm are indeed very relative. Therefore, educators usually use measuring tools in the form of test or non-test techniques, depending on what is to be measured, or what information will be collected